The Distinct Roles of CXCR3 Variants and Their Ligands in the Tumor Microenvironment - Nathan Reynders; Dayana Abboud; Alessandra Baragli; Muhammad Zaeem Noman; Bernard Rogister; Simone P. Niclou; Nikolaus Heveker; Bassam Janji; Julien Hanson; Martyna Szpakowska; Andy Chevigné (Cells, 2019)
First thought to orchestrate exclusively leukocyte trafficking, chemokines are now acknowledged for their multiple roles in the regulation of cell proliferation, differentiation, and survival. Dysregulation of their normal functions contributes to various pathologies, including inflammatory diseases and cancer. The two chemokine receptor 3 variants CXCR3-A and CXCR3-B, together with their cognate chemokines (CXCL11, CXCL10, CXCL9, CXCL4, and CXCL4L1), are involved in the control but also in the development of many tumors. CXCR3-A drives the infiltration of leukocytes to the tumor bed to modulate tumor progression (paracrine axis). Conversely, tumor-driven changes in the expression of the CXCR3 variants and their ligands promote cancer progression (autocrine axis). This review summarizes the anti- and pro-tumoral activities of the CXCR3 variants and their associated chemokines with a focus on the understanding of their distinct biological roles in the tumor microenvironment.